New checklist and the red list of the mosses (Bryophyta) of Slovenia - Martinčič, Andrej (Hacquetia, 2024)
The new Checklist of mosses (Bryophyta) of Slovenia within current political boundaries comprises 667 species, 6 subspecies and 18 varieties. Aditional 13 species are denoting by a question mark since reports are considered questionable for whatever reason. An alphabetically arranged tabular presentation of genera and species, as well as lower taxa, also shows their presence in individual phytogeographical units of Slovenia. Corresponding symbols present records from the period before and after 1959. Each species has also Red List status in Slovenia. The Checklist includes the data from literature and LJU herbarium. Annotations give a critical evaluation of special literature and herbarium data. A list of taxa that should be excluded from the flora of Slovenia and the synonyms used in the floristic literature for Slovenia are also added.